Complement and Coagulation - Tomar, R. H; Kolchins, Diane (Thrombosis and Haemostasis, 1972)
Serum β1c- β1a was found to be significantly depressed in 16 of 27 patients with disseminated intravascular coagulation. In vitro studies supported the finding that the serum β1c- β1a of urokinase-treated patients was not altered by fibrinolytic therapy. This strongly suggests that plasmin is not responsible for the low C3.